Sequential Decisions and Compensatory Tendencies: Evidence from Camogie - Eakins, John; Considine, John; Collins, Niall; Horgan, Peter; Weir, Conor (The Economic and Social Review, 2025)
Research on the decision-making of officials in Gaelic Games is sparse and limited to the male game. This paper goes a small way to addressing this gap by examining referee decisions to award frees in the game of camogie, the female version of the game of hurling. It is hypothesised that these decisions are biased toward the team behind on the scoreboard and behind on the cumulative difference in frees awarded. Using data from 136 camogie games across eight seasons, and a series of probit estimations, we find evidence of the presence of such compensatory tendencies. We also find that home bias is not an underlying explanation for the presence of these compensatory tendencies. These findings are consistent with previous research on hurling. This paper advances the analysis by conducting a similar investigation on sideline awards by sideline officials as a benchmark for comparison. These results show no statistical relationship between the award of sidelines and the scoreboard. This comparison strengthens that case that the discretionary nature of the decision to award frees by the referee is the channel through which the compensatory tendencies operate. These decisions are rationalised on the basis that referees in camogie prioritise game-management over accuracy.